A high efficiency, high quality and low cost internal regulated bioanalytical laboratory to support drug development needs. (May 2014) - Song, Yan; Dhodda, Raj; Zhang, Jun; Sydor, Jens
In the recent past, we have seen an increase in the outsourcing of bioanalysis in pharmaceutical companies in support of their drug development pipeline. This trend is largely driven by the effort to reduce internal cost, especially in support of late-stage pipeline assets where established bioanalytical assays are used to analyze a large volume of samples. This article will highlight our perspective of how bioanalytical laboratories within pharmaceutical companies can be developed into the best partner in the advancement of drug development pipelines with high-quality support at competitive cost.